Mr. Penguin and the catastrophic cruise - Smith, Alex T. (Smith, Alex T., Mr. Penguin, 2020)
Mr. Penguin is boarding a luxury cruise ship. He doesn't like water, and he can't swim, but his friend Colin is performing with the Ladies Choir on board - and anyway, Mr, Penguin feels like a rest after some busy Adventuring. What's more, fish finger sandwiches are apparently available twenty-four hours a day. Heaven! But despite the glamorous film stars and party atmosphere, Mr Penguin can't help but feel that something shifty is happening on board. And when he befriends a young stowaway with a mystery of her own to solve, he soon finds that Adventures are lying in wait after all ...